(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT This study explores the profound impact of Marxism on 20th-century literary criticism, highlighting its emergence as a critical framework that reshaped literary theory and analysis. Beginning with the foundational texts of Karl Marx and Friedrich Engels, the paper examines how Marxist theory, particularly the concepts of class struggle, ideology, and historical materialism, influenced critical approaches to literature. Key figures such as Georg Lukas’s, Antonio Gramsci, and later, the Frankfurt School, are analyzed for their contributions to the intersection of literature and socio-political critique. The analysis also addresses the adaptation of Marxist thought in various literary movements, including socialist realism and post-colonial literature. Additionally, the paper considers critiques of Marxism within literary studies, exploring tensions between ideology and aesthetic form. Ultimately, the study underscores the lasting legacy of Marxist criticism in shaping contemporary literary discourse and its ongoing relevance in addressing issues of power, representation, and social justice in literature.